Peningkatan Kemampuan Menulis Publikasi Ilmiah Guru Melalui Coaching Clinic - Deni Kadarsah (Jurnal Administrasi Pendidikan, 2022)
This study aims to analyze  the improvement of teachers' scientific  publication writing skills through coaching clinics. The research design used School Action Research which consisted of four stages of activity: planning, acting, observing, and reflecting. The subjects of this study were teachers in the UPI Pilot Laboratory SMAS environment, totaling 44 people. The results showed that the application of the coaching clinic was able to improve the ability to write scientific publications for teachers at the UPI Pilot Laboratory SMAS. Based on the results of observations, the role of coaching clinics in writing scientific publications can be done as long as the Principal has the commitment and ability to do so. Based on the test results on the ability to write scientific publications, the teachers themselves show that there is an average positive score, which is 46.18 with a success percentage of 54.55% in Cycle I and an average of 56.91 points with a success percentage of 72. ,73% in Cycle II. The responses of the teachers to the implementation of the coaching clinic in writing this scientific publication were very positive, as shown by the results of the questionnaire distributed by researchers to teachers.